TRADITIONAL STORIES AND LEGENDS WITHIN THE REALM OF LITERARY ANALYSIS (Ustozlar uchun, 2024)
Abstract: This article examines the importance of traditional narratives and myths within the realm of literary critique. It investigates the influence of folklore on the formation of cultural identities, the shaping of narrative frameworks, and the enhancement of literary motifs. By scrutinizing a range of literary compositions, this research elucidates the lasting influence of folkloric tales on narrative conventions and the interpretation of literary works.